The effects of exercise intensity and post-exercise recovery time on cortical activation as revealed by EEG alpha peak frequency. (6th March 2018) - Gutmann, B.; Zimmer, P.; Hülsdünker, T.; Lefebvre, J.; Binnebößel, S.; Oberste, M.; Bloch, W.; Strüder, H.K.; Mierau, A.
Highlights: Exhaustive exercise induces a transient increase of the iAPF for about 30 min. Intense exercise (>85% of maximum heart rate) is required to increase the iAPF. The increased iAPF following physical exercise may facilitate cognitive function. Abstract: Acute physical exercise (APE) induces an increase in the individual alpha peak frequency (iAPF), a cortical parameter associated with neural information processing speed. The aim of this study was to further scrutinize the influence of different APE intensities on post-exercise iAPF as well as its time course after exercise cessation. 95 healthy young (18–35 years) subjects participated in two randomized controlled experiments (EX1 and EX2). In EX1, all participants completed a graded exercise test (GXT) until exhaustion and were randomly allocated into different delay groups (immediately 0, 30, 60 and 90 min after GXT). The iAPF was determined before, immediately after as well as after the group-specific delay following the GXT. In EX2, participants exercised for 35 min at either 45–50%, 65–70% or 85–90% of their maximum heart rate (HRmax ). The iAPF was determined before, immediately after as well as 20 min after exercise cessation. In EX1, the iAPF was significantly increased immediately after the GXT in all groups. This effect was not any more detectable after 30 min following exercise cessation. In EX2, a significant increase of the iAPF was found only after high-intensity (85–90% HRmax ) exercise. The results indicate intense or exhaustive physical exercise is required to induce a transient increase in the iAPF that persists about 30 min following exercise cessation. Based on these findings, further research will have to scrutinize the behavioral implications associated with iAPF modulations following exercise.